2018
DOI: 10.1177/0265532218758127
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes professional communication in aviation: Is language proficiency enough for testing purposes?

Abstract: This paper aims to identify what aviation experts consider to be the key features of effective communication by examining in detail their commentary on a 17-minute segment of recorded radiotelephony discourse between a Russian pilot and a Korean air traffic controller. The segment was played to three practising pilots and three air traffic controllers. Their commentary on the qualities of communication displayed in the interaction was recorded and coded thematically, using a grounded ethnography approach. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 28 publications
1
31
0
5
Order By: Relevance
“…In a comparison between a radio communication corpus and a professional radio broadcaster's corpus, Trippe and Baese-Berk (2019) concluded that pilots and controllers tend to have a faster speech rate. Kim (2018) conducted a study with six professionals, analyzing their perceptions of a real communication between a Russian pilot and a Korean controller. The professionals recognized that despite clear linguistic limitations, the pilot acted professionally and handled the communication effectively, whereas the controller, even though he demonstrated a higher linguistic level, did not show the same experience in dealing with the problem, thus overloading the pilot.…”
Section: Oral Elements In Aeronautical Englishmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparison between a radio communication corpus and a professional radio broadcaster's corpus, Trippe and Baese-Berk (2019) concluded that pilots and controllers tend to have a faster speech rate. Kim (2018) conducted a study with six professionals, analyzing their perceptions of a real communication between a Russian pilot and a Korean controller. The professionals recognized that despite clear linguistic limitations, the pilot acted professionally and handled the communication effectively, whereas the controller, even though he demonstrated a higher linguistic level, did not show the same experience in dealing with the problem, thus overloading the pilot.…”
Section: Oral Elements In Aeronautical Englishmentioning
confidence: 99%
“…In language testing, particularly in the field of English for Specific Purposes (ESP), Douglas (1999) argues that real-life tasks should be implemented in language proficiency tests as a means of truly and fairly analyzing the candidates' production. This has shown to be highly relevant in aviation English studies such as Kim (2018), which compares the language production of both novice and experienced air traffic controllers and pilots: the more experienced the professional, the better the performance when assessed in real-life tasks.…”
Section: Introductionmentioning
confidence: 99%
“…“English: The Language of the Skies” is the motto of the ICAEA, the International Civil Aviation English Association, which develops workshops and tools, once again, to “harmonize” the use of standard aviation phraseology across the globe, particularly among the air traffic controllers and pilots whose first language is not English. Expert discourses often attribute accidents to poor English proficiency rather than factors such as inadequate training or other forms of miscommunication (Estival, Farris, and Molesworth 2016; Kim 2018). These discourses of standardization can prove paternalizing.…”
Section: On‐time Performances: Institutions and Infrastructurementioning
confidence: 99%
“…In flight training, it is likely that a NNES flight student will interact with NES air traffic controllers and instructors. In RTF communications, Bieswanger (2013) and Kim (2018) highlighted a frequent lack of adaptation and accommodation strategies used by the NES. In busy airspace which includes heavy flight training activity, controllers may experience frustration in communicating with NNES student pilots, believing it adds to their workload and causes congestion on the frequencies.…”
Section: Native English Speaker and Non-native English Speaker Interamentioning
confidence: 99%